Oncolytic Newcastle disease virus for cancer therapy: old challenges and new directions. (March 2012) - Zamarin, Dmitriy; Palese, Peter
Newcastle disease virus (NDV) is an avian paramyxovirus, which has been demonstrated to possess significant oncolytic activity against mammalian cancers. This review summarizes the research leading to the elucidation of the mechanisms of NDV-mediated oncolysis, as well as the development of novel oncolytic agents through the use of genetic engineering. Clinical trials utilizing NDV strains and NDV-based autologous tumor cell vaccines will expand our knowledge of these novel anticancer strategies and will ultimately result in the successful use of the virus in the clinical setting.